2004
DOI: 10.1063/1.1844598
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of enhanced residual thermal energy coupling to solids in femtosecond laser ablation

Abstract: We perform direct measurement of the thermal energy remaining in the bulk of Cu, Mg, Au, and Si samples following multi-pulse femtosecond laser ablation. In contrast to the previous belief that the thermal energy remaining in the ablated sample is negligible using femtosecond pulses, we show a significant amount of residual thermal energy deposited in various materials. In fact, with a sufficiently large number of pulses at high fluence, virtually all the incident laser energy can be retained in the sample. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 9 publications
1
49
0
1
Order By: Relevance
“…Although femtosecond laser ablation have been extensively studied in the past [21][22][23][24][25][26][27], many of the physical mechanisms remain unclear. For example, recent studies have shown that the residual thermal energy in an irradiated metal sample abruptly increases following both single-pulse and pulse-train femtosecond laser ablation in a gas medium when the laser fluence is above a certain threshold [28,29]. In the case of pulse-train ablation [29], it was found that one contributing factor to the enhanced thermal coupling following a large number of applied pulses is an increase of sample absorptance due to surface structural modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although femtosecond laser ablation have been extensively studied in the past [21][22][23][24][25][26][27], many of the physical mechanisms remain unclear. For example, recent studies have shown that the residual thermal energy in an irradiated metal sample abruptly increases following both single-pulse and pulse-train femtosecond laser ablation in a gas medium when the laser fluence is above a certain threshold [28,29]. In the case of pulse-train ablation [29], it was found that one contributing factor to the enhanced thermal coupling following a large number of applied pulses is an increase of sample absorptance due to surface structural modifications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have shown that the residual thermal energy in an irradiated metal sample abruptly increases following both single-pulse and pulse-train femtosecond laser ablation in a gas medium when the laser fluence is above a certain threshold [28,29]. In the case of pulse-train ablation [29], it was found that one contributing factor to the enhanced thermal coupling following a large number of applied pulses is an increase of sample absorptance due to surface structural modifications. However, we have shown that the surface modifications alone cannot fully explain the enhanced thermal energy deposition [29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we observe that the repetition rate has no major effect on the ablation efficiency in fluence [µm 3 pls -1 J -1 cm²] since all data points are located on the same tendency curve. However, the repetition rate has a significant effect on the ablation efficiency in power [mm 3 min -1 W -1 ] since we observe a positive effect on Al and Mo between 250kHz to 1MHz (no effect above) and a negative effect on Copper.…”
Section: Resultsmentioning
confidence: 95%
“…Depositing more energy into the target could increase ablation efficiency [2], thanks to heat accumulation [3], but could as well introduce detrimental effect on processing quality [2]. Finally, the response of the material highly depends on its thermo-physical properties and its capacity to cope with the thermal load.…”
Section: Introductionmentioning
confidence: 99%
“…Norris et al, 2003;Eesley, 1983;Tas & Maris, 1994), but most of these studies are performed at relatively low excitations. Absorption measurements have been done at very high fluencies for studying the dynamics of electrons in the plasma state (Milchberg et al, 1988;Cerchez et al, 2008) and the energy that resides in the sample after laser ablation (Vorobyev & Guo, 2004). However, at a more moderate excitation, where processes such as melting and desorption occur, the change in absorption can still be significant, but they are often neglected.…”
Section: Non-linear Heating By a Single Laser Pulsementioning
confidence: 99%